2002
DOI: 10.1897/1551-5028(2002)021<1679:tomtbe>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Methyl Tert-Butyl Ether to Plants (Avena Sativa, Zea Mays, Triticum Aestivum, and Lactuca Sativa)

Abstract: Influence of methyl tert-butyl ether (MTBE) on the germination of seeds and growth of seedling plants were studied in laboratory experiments. Test plants were wild oats (Avena sativa), sweet corn (Zea mays), wheat (Triticum aestivum), and lettuce (Lactuca sativa). Seed germination, shoot growth, and root growth of plants exposed to different concentrations of MTBE in a moist soil were examined. Seed germination and seedling growth in MTBE-contaminated soil were markedly reduced in all test plants. The median l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
2

Year Published

2006
2006
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
2
8
2
Order By: Relevance
“…The results with Lactuca sativa seeds in the concentration range resembling the possible real concentration in soil proved acute toxicity of MTBE on this plant after evaluation by Dunnett's method. Our data are in general agreement with previous study (An et al, 2002). An et al (2002) measured MTBE toxicity by the germination of seeds (Avena sativa, Zea mays, Triticum aestivum, and Lactuca sativa) in soil and using this contact system they detected rather high toxic effect in the same period and they found that EC 50 for Lactuca sativa roots was 29 mg (MTBE)/kg soil.…”
Section: Seeds Testsupporting
confidence: 94%
See 1 more Smart Citation
“…The results with Lactuca sativa seeds in the concentration range resembling the possible real concentration in soil proved acute toxicity of MTBE on this plant after evaluation by Dunnett's method. Our data are in general agreement with previous study (An et al, 2002). An et al (2002) measured MTBE toxicity by the germination of seeds (Avena sativa, Zea mays, Triticum aestivum, and Lactuca sativa) in soil and using this contact system they detected rather high toxic effect in the same period and they found that EC 50 for Lactuca sativa roots was 29 mg (MTBE)/kg soil.…”
Section: Seeds Testsupporting
confidence: 94%
“…Our data are in general agreement with previous study (An et al, 2002). An et al (2002) measured MTBE toxicity by the germination of seeds (Avena sativa, Zea mays, Triticum aestivum, and Lactuca sativa) in soil and using this contact system they detected rather high toxic effect in the same period and they found that EC 50 for Lactuca sativa roots was 29 mg (MTBE)/kg soil. Then our data were evaluated according to Czech legislative (Anonymous, 1998b).…”
Section: Seeds Testsupporting
confidence: 94%
“…Chugh and Sawhney [32] also observed similar influence of cadmium toxicity on germinating seeds of pea. Not only Cd but also low levels of other heavy metals like Cu and Pb have stimulating effect on seed germination [33][34][35][36]. However, in case of their wild relative, although 100 M of Cd slightly enhanced the seed germination percentage but as a whole Cd did not positively influence the seed germination percentage as compared to control.…”
Section: Effect Of CD Treatments On Plant's Qualitative and Quantitatmentioning
confidence: 89%
“…Toxicity was found to be slightly higher for rainbow trout (Oncorhynchus mykiss) [30]. In a study by An et al [31], the combined LC 50 and EC 50 -values for lettuce (Lactuca sativa), wild oats (Avena sativa), wheat (Triticum aestivum), and sweet corn (Zea mays) were in the range of 18-91, 362-459, 432-751, and 672-964 mg MTBE kg −1 soil (dry wt), respectively, when growth of shoots and roots was used as the sensitive end points. Results from the current study indicated that weeping willows seem to be less sensitive than other species tested before.…”
Section: Phytotoxicity Of Mtbe To Weeping Willows In Hydroponic Solutionmentioning
confidence: 99%